Reliability of squat kinetics in well-trained rugby players - Appleby, B. B.; Cormack, S. J.; Newton, R. U. (The Journal of Strength and Conditioning Research, 2019)
The aim of this study was to determine the within-session reliability in kinetic variables of the squat in well-trained athletes during a typical resistance training protocol. Fifteen subjects completed 2 testing sessions. Session 1 was establishment of 1 repetition maximum (1RM) squat, and session 2 involved 2 sets of 2 maximal effort repetitions of the squat at 70, 80, and 90% of 1RM with 3D motion analysis and ground reaction force (GRF) measurement using 2 in-ground triaxial force plates. Reliability was calculated using typical error ± 90% confidence limits, expressed as the coefficient of variation and intraclass correlation coefficient. The smallest worthwhile change (SWC%), calculated as 0.2 × between-subject SD, was used to determine the smallest important change in performance. Peak GRF and average GRF were found to have acceptable measures of reliability with the combined left and right leg average GRF capable of detecting the SWC. Independent limb contributions were reliable (left and right, or dominant and nondominant). Reliable kinetics can be obtained in back squat performance typical of a resistance training session in well-trained athletes. This suggests that coaches integrating force plate technology within training sessions may effectively capture between 1 and 6 training sets among several athletes, facilitating analysis and intervention on larger data sets.The aim of this study was to examine the correlation between muscle fiber type and sprint performance in elite young soccer players of different age groups of the same team. Twenty-eight young players participated in this study (group U15, n = 8; group U13, n = 9; and group U11, n = 11). Anthropometric assessments, acceleration (10 m), and Bangsbo modified sprint test (30 m) were performed. Muscle biopsies were obtained from the vastus lateralis, and after that, fiber-type composition was determined by immunohistochemistry. No significant correlations were found between the sprint test and muscle fiber distribution for the groups U13 and U11 (p > 0.05). Also, no correlations were found between cross-sectional areas in the types of fibers with the sprint test in all groups (p > 0.05). A positive correlation was found between type I fibers and the performance in the acceleration test (10 m) (r = 0.77, p < 0.05) was found only in group U15 and a negative correlation between type IIA fibers and the performance in the acceleration test (10 m) (r = 0.89, p < 0.05). The correlations were observed only in group U15, which may indicate that the duration and the intensity of the soccer systematic training can affect the plasticity of the muscle fibers. Specific soccer training in youth is one of the factors that can affect fiber-type plasticity. The specific training programs and status of U15 are more intensive, and the exercises are oriented more to improve physical fitness.